Relationship Between Intimate Partner Violence and Quality of Life Among Women With Chronic Diseases: Mediating and Moderating Role of Sense of Coherence - Bagherzadeh, Razieh (Violence against women, 2026)
This study examined the mediating and moderating roles of the sense of coherence (SOC) on the relationship between intimate partner violence (IPV) and quality of life (QOL) in women with chronic diseases. Structural equation modeling was conducted on data from 400 women with chronic diseases. The moderating effect was not statistically significant. The mediating model indicates that SOC partially mediates the relationship between IPV and both mental (direct effect = −0.313; indirect effect = −0.147) and physical (direct effect = −0.258; indirect effect = −0.100) QOL. IPV, both directly and indirectly through a negative impact on SOC, reduces QOL among women with chronic diseases.